Risk of congenital toxoplasmosis in women with low or indeterminate anti-Toxoplasma IgG avidity index in the first trimester of pregnancy: an observational retrospective study. (June 2019) - Tomasoni, L.R.; Messina, G.; Genco, F.; Scudeller, L.; Prestia, M.; Spinoni, V.; Bonfanti, C.; Prefumo, F.; Castelli, F.; Meroni, V.
Abstract: Objectives: Congenital toxoplasmosis (CT) affects one to ten fetuses per 10 000 live newborns in western countries. Without knowing pre-conception serostatus, it is hard to date the infection when anti- Toxoplasma IgG and IgM antibodies are positive at first screening. Although a high IgG avidity index (AI) in the first trimester excludes CT, the same cannot be said of intermediate and low AI. The aim of this study was to estimate the risk of CT when intermediate or low AI is detected in the first trimester of pregnancy. Methods: Our observational retrospective study enrolled women with positive anti- Toxoplasma IgG and IgM, and low/intermediate AI in the first trimester of gestation seen at two reference centres in northern Italy between 2006 and 2015. All women received spiramycin. When requested by women, a sample of fluid obtained through amniocentesis was tested with a commercial real-time PCR. CT was defined by positive PCR result confirmed on aborted materials or by newborn follow up. Results: Overall, 778 first-trimester pregnant women were included; AI was low in 532/778 (68%) and intermediate in 246/778 (32%). Amniocenteses were performed in 528/778 (67.9%), with no fetal loss. In all, 19/778 (2.4%) miscarriages and 15/778 (1.9%) pregnancy terminations were recorded; 9/778 (1.6%) were lost to follow up. In two women, PCR on amniotic fluid was positive, but CT was confirmed in only 1/747 cases (0.13%, 95% CI 0.02%–0.75%). Conclusion: In our study, the risk of CT was much lower than anticipated. These data must be considered when counselling these women.